Creating inequality in accessibility: The relationships between public transport and social housing policy in deprived areas of Santiago de Chile. (February 2018) - Martínez, Cristhian Figueroa; Hodgson, Frances; Mullen, Caroline; Timms, Paul
Abstract: This paper identifies the very limited connectivity provided by the current public transport system to the most deprived groups of Santiago de Chile, and explores the territorial aspects of transport and social housing policies that have contributed to the creation of unequal public transport schemes. To achieve those aims, we present a review of public policies in Chile and the results of an original quantitative analysis that measures the travel times required to access the opportunities and activities located in the city. The results show that housing policies put people at a disadvantage by increasing the distance between them and the opportunities of the city. Three decades after the implementation of housing policies, transport still fails to mitigate these distances and instead of alleviating the patterns of segregation, it may have reinforced them. The travel times required increase towards the periphery (even though densities do not decrease) and are higher than the averages of the city in social housing estates. Highlights: Provides a quantitative analysis of the relationship between housing and transport policies Measures access travel times for Santiago de Chile as a whole, and compares these with travel times to deprived settlements Finds access travel times are higher than the averages in social housing estates built by public policies Finds evidence that housing and transport policy have led to transport disadvantage, social exclusion and transport poverty